LEGAL ASPECTS OF DIGITAL BANKING - Jovan Sreckovic (Pravo)
The rapid development of digital banking has fundamentally transformed the capabilities of the financial sector, offering a range of new opportunities and challenges. This paper explores the legal aspects of the transformation of the financial sector through digital banking. It analyzes the regulatory framework that impacts the development and implementation of digital banking services, focusing on key laws, regulations, and legal standards that shape this area. The paper also addresses issues of data security, privacy protection, user authentication, and liability in cases of fraud or abuse. The research aims to provide deeper insights into the legal challenges and opportunities arising from the digital transformation of the financial sector, as well as identify potential legal frameworks and strategies for improving the efficiency and transparency of digital banking. The paper further examines the impact of digital banking on traditional banking practices, including customer service, operational efficiency, and revenue-generation models. Special attention is given to exploring the implications of digital banking for financial inclusion, particularly in underserved and remote communities, and its role in fostering economic development.